An overview of attacks against digital watermarking and their respective countermeasures - Tanha, Maryam; Torshizi, Seyed Dawood Sajjadi; Abdullah @ Selimun, Mohd Taufik; Hashim, Fazirulhisyam (IEEE, 2012)
The increased and widespread usage of digital multimedia has aroused great concerns regarding issues such as copyright protection, copy control and proof of ownership. Digital watermarking serves as a solution to these kinds of problems; however, digital watermarking techniques have demonstrated to possess vulnerabilities. Thus opening avenues for malicious attackers to abuse these security breaches. Therefore, maintaining the security of digital watermarked media i.e. text, image, audio and video has received considerable attention. This paper has conducted a comprehensive research with special emphasis on the classification of malicious attacks against digital watermarking. Subsequently, it reviews the current countermeasures available to mitigate the intentional attacks. In addition, it procures a foundation for the evaluation of various watermarking algorithms.